Practical realisation of multiband planar filters on multilayer substrates - Nepaya, Leokadia Ndeapo Popyeni (Department of Electrical Engineering, 2019)
This research presents the design of planar microwave filters implemented on microstrip multi-layer technology. These should be able to attain and realize specified essential requirements such as multi-band operation, compact size, and without significant deteriorated filter performance in comparison with single-band filters. The focus is placed on new synthesis and design procedures for multiband responses. In some cases, the possibility to include re-configurable characteristics of these filters is required. The focus of the research is entirely on examining the properties and implications of a previously proposed reactance transform method for multiband filter synthesis. The research commences with reviews of multi-band filter synthesis methods. The research specifically examines a full analytical synthesis approach based on reactance transforms method and the implications for practical design approaches Investigations on narrowband with coupled resonator filters representation and wide-band with quasi-lumped element filters representation of up to quad-bands based on reactance transform method are undertaken. With the emphasis on practical aspects such as losses and selectivity, which are related to the physical implementation on multi-layer substrate, the key differences between multiband and single-band filters based on a reactance transform are highlighted. It is illustrated that, in addition to the order of the basis filter, selectivity is influenced by the number of bands, the spacing of the bands and the relative bandwidths. It is also shown that loss has a significant effect on multiband filter responses, in a somewhat different way from that for single-band filters. Physical designs of narrow- band coupled resonators filters are implemented with the aim of examining the degrees of design freedom for multi-layer substrate design, considering the resonance properties and couplings between resonators and considering loss for resonators on different layers. Mercurywave 9350, a low-cost multi-layer substrate is chosen and deemed suitable for a number of reasons, including relatively constant permittivity over frequency. The designs consist of novel topologies: parallel connected multi-path referred to as transversal and also all-pole topologies. A transversal topology includes a dual-band dual-path design as well as a dual-band triple-path design while the all-pole topology is a quad-band design. The research explores re-configurable characteristics of narrow-band coupled resonators of a dual-band dual-path design. A process to obtain a re-configurable multi-band filter with electronically selected pass-bands, based on a reactance transform method for coupled resonator filters, is described. A dual-band multi-band filter realized on multi-layer substrate is designed for passive space applications and reconfigurability is demonstrated using a pre-selection method. For wide-band, quasi-lumped element filters are realized on multi-layer substrate, the inductors are implemented as rectangular spiral inductors and Capacitors as broadside coupling plates connected from two different layers through metallic vias. Parasitic that may influence the relative bandwidths.